Coping with HIV Stigma among People Living with HIV in Yogyakarta, Indonesia: A Mixed-Methods Approach - Reni Puspitasari; Jerome V. Cleofas (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: People living with HIV are related to experience stigma and discrimination. Stigma can disrupt mental health and PLHIV have coping strategies to overcome internalize stigma. This study aimed to describe how PLHIV cope with HIV stigma.Methods: This study used explanatory design. The quantitative data were collected to describe the internalized HIV stigma with 100 participants using a questionnaire and analyzed using multiple regressions. The qualitative data from the second phase were used to build on or explain the qualitative data with 14 participants using purposive sampling method and analyzed using thematic analysis.Results: The participants reported to have low extent of internalized HIV stigma (mean=1.80) and the highest item was feeling guilty (mean=2.2) using quantitative analysis. The demographic profile were not significant predictors of internalized HIV stigma. The result from qualitative analysis was the coping internalized HIV stigma among PLHIV divided by negative and positive coping stigma, such as emotional and cognitive coping, behavior coping, social coping.Conclusion: PLHIV have low extent of internalized stigma. The coping internalized HIV stigma among PLHIV was divided by negative and positive coping stigma.